An unexpected digital papillary adenocarcinoma of the thumb*. Issue 1 (1st January 2016) - Nash, Mitchell; Burn, Juliet; Chan, Simon
Abstract: Digital papillary adenocarcinoma (DPAca) is an aggressive lesion with high metastatic potential, which is easily misdiagnosed. We present a 55-year-old male with a cystic lesion on his right thumb. Above all else, lesions of the digits should be sent for histopathology routinely, regardless of their history or appearance.